2018
DOI: 10.1159/000489373
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Nrf2 Promotes Schwann Cell-Mediated Sciatic Nerve Recovery in Diabetic Peripheral Neuropathy

Abstract: Background/Aims: High glucose-induced oxidative stress and inflammatory responses play an important role in painful diabetic neuropathy by activating the TLR4/NFκB signal pathway. Schwann cells (SCs) are integral to peripheral nerve biology, contributing to saltatory conduction along axons, nerve and axon development, and axonal regeneration. SCs provide a microenvironment favoring vascular regeneration but their low survival ratio in hyperglycemic conditions suppress the function to promote nerve growth. Nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Meanwhile, a previous study verified that Nrf2 expression inhibits hyperglycemia-induced peripheral nerve injury by suppressing the TLR4/NF-κB signaling pathway [ 50 ]. The expression of Nrf2 also suppresses TLR4/NF-κB-mediated inflammatory cytokine expression [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, a previous study verified that Nrf2 expression inhibits hyperglycemia-induced peripheral nerve injury by suppressing the TLR4/NF-κB signaling pathway [ 50 ]. The expression of Nrf2 also suppresses TLR4/NF-κB-mediated inflammatory cytokine expression [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 pathway activation initiates the transcriptional regulation of ARE‐dependent expression of diverse anti‐oxidants and phase II detoxification enzymes, including heme oxygenase‐1 (Ho‐1) and nicotinamide adenine dinucleotide (phosphate) H quinone oxidoreductase 1 (Nqo1). Furthermore, the overexpression of Nrf2 reportedly inhibits apoptosis that is induced by high glucose in Schwann cells, and the transplantation of Nrf2‐overexpressing Schwann cells can recover nerve functions in diabetic animals. Therefore, Nrf2 has become a therapeutic target in diabetic peripheral neuropathy.…”
Section: Introductionmentioning
confidence: 99%
“…The vascular complications of diabetic neuropathy involve impaired endoneurial blood flow to the peripheral nerves, leading to the destruction of neurons and Schwann cells (SCs) [ 58 ]. Overexpression of Nrf2 may repair nerve injury as Tang et al reported that SCs overexpressing Nrf2 restored nerve conduction velocity, myelin sheath thickness, and sciatic vasa nervorum while also inhibiting hyperglycemia-induced apoptosis [ 59 ]. Further, overexpressing Nrf2 promoted angiogenesis by regulating the Toll-like receptor 4/NF-κB signaling pathway in a rodent model of diabetic neuropathy [ 59 ].…”
Section: Nrf2 Signaling and Its Inducers In Different Peripheral Neur...mentioning
confidence: 99%